Three ways to be brave : a trio of stories - Clark, Karla (Karla Jean) (Rise x Penguin Workshop, 2021)
In this collection of rhyming stories, children conquer their fears and find inner strength during a nighttime thunderstorm, the first day of school, and a doctor's visit.